Two new species of Comesomatidae (Nematoda) from the East China Sea - Huang, Mian; Huang, Yong (Zootaxa, 2018)
Two new free-living marine nematode species of the genus Paracomesoma and genus Metacomesoma belonging to family Comesomatidae are described from the sublittoral sediment of the East China Sea. Paracomesoma zhangi sp. nov. is characterized by cuticle with fine transverse rows of dots, without lateral differentiation; buccal cavity with three small teeth; cephalic setae 13.5 μm long; multispiral amphideal fovea with three turns; spicules slender and elongated with thick cuticularized proximal end; gubernaculum plate-like without apophysis; 26 minute precloacal supplements. Metacomesoma macramphida sp. nov. is characterized by very small buccal cavity without teeth; inner and outer labial sensilla papilliform; four cephalic setae 1.5 μm long; multispiral amphideal fovea large, with 4.5 turns; spicules slender and elongated, with cephalated proximal end and finger-shaped distal end; gubernaculum plate-like, without apophysis; precloacal supplements absent. An updated dichotomous key for the identification of the males of the species of Paracomesoma is provided.